Development of Study on Heat Transfer and Friction Characteristics of Fin-and-Tube Heat Exchanger-Experimental Study - 刘建; 魏文建; 丁国良; 张春路 (Zhileng xuebao)
This paper reviews the recent development of the study on heat transfer and friction characteristics of fin-and-tube exchangers with different fin surfaces. The fin surface types involve in plain fin surface, corrugated fin surface, silt fin surface, and louver fin surface. By stating and analyzing the heat transfer and friction characteristics with different fin surfaces the feature and application with special fin surface are described and the methods of improvement are suggested.